Does Philosophy Require De-Transcendentalization? Habermas, Apel, and the Role of Transcendentals in Philosophical Discourse and Social-Scientific Explanation - Michalska, Anna (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2019)
The heritage of transcendental philosophy, and more specifically its viability when it comes to the problematic of the philosophy of social sciences, has been a key point of dissensus between Jürgen Habermas and Karl-Otto Apel. Whereas Apel has explicitly aimed at a transcendental-pragmatic transformation of philosophy, Habermas has consequently insisted that his formal pragmatics, and the theory of communicative action which is erected upon it, radically de-transcendentalizes the subject. In a word, the disagreement concerns whether transcendental entities have any substantial role to play in philosophical discourse and social-scientific explanations. My aim is to reconstruct how Apel establishes a connection between transcendentals, qua the ideal communicative community and the possibility of non-objectifying self-reflection. As I shall demonstrate, the principles that transcendental pragmatics sees as underlying social actions are not to be understood in a strictly judicial way, as “supernorms.” Rather, they should be conceptualized and used as a means for action regulation and mutual action coordination. Against this backdrop, I show that the concept of the ideal community provides the necessary underpinnings for Habermas’ schema of validity claims and the project of reconstructive sciences.